Alle origini della Questione Meridionale: Nazione e mezzogiorno di Giacomo Tarascio - Fresu, Gianni (International Gramsci Journal, 2023)
This is the abstract of a review in Italian by Gianni Fresu of the book by Giacomo Tarascio, Nazione e mezzogiorno. (Roma, Ediesse 2016).